Hardware Asset Recording Information System Based on Web at PT. ABC: Sistem Informasi Pencatatan Aset Perangkat Berbasis Web di PT. ABC - Syah, Naufal Galfan; Fitrani, Arif Senja (Procedia of Engineering and Life Science, 2024)
PT. ABC is an IT company that focuses on the design, development, and maintenance of LAN and WAN networks, network routers, and websites. The company has many assets in the form of computer network devices that need to be recorded meticulously. Currently, asset recording is still done manually using Google Spreadsheet, which is considered less effective and time-consuming. In the rapidly evolving digital era, the utilization of technology and information systems has become crucial. The proper use of information systems can enhance efficiency in managing asset data and facilitate information access. Therefore, PT. Smart Connect requires further improvement in its information system for asset recording and reporting. The goal is to expedite the asset recording process and provide more detailed reports, thereby increasing efficiency and productivity in company asset management.